Implementasi Penerapan Good Corporate Governance Pada PT. Bank Muamalat KCP Stabat - M. Iqbal; Mhd Rizki Khairi; Muhammad Hasan Asy Ary; Ahmad Firdaus Lingga (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research explores the implementation of Good Corporate Governance (GCG) at Bank Muamalat KCP Stabat. The findings show that the bank has succeeded in establishing a strong corporate governance structure, with the active involvement of the supervisory board and audit committee, which reflects a commitment to transparency and accountability. Bank management is considered as a reliable agent, in accordance with the principles of Agency Theory, creating positive tendencies in policies that support the interests of shareholders. In the dimensions of Stewardship Theory, banks actively integrate the interests of customers, employees and society into their GCG policies, showing the importance of a corporate culture that supports management's stewardship role. The success of GCG implementation is realized in achieving compliance with regulations and standards, with transparent financial reports. Bank Muamalat KCP Stabat, through its GCG practices, has a positive impact on shareholders and other stakeholders.